Advances in nano-delivery systems for doxorubicin: an updated insight - Kanwal, Ummarah; Irfan Bukhari, Nadeem; Ovais, Muhammad; Abass, Nasir; Hussain, Khalid; Raza, Abida (Journal of drug targeting, 2018)
Doxorubicin (DOX) is the most effective chemotherapeutic drug developed against broad range of cancers such as solid tumours, transplantable leukemias and lymphomas. Conventional DOX-induced cardiotoxicity has limited its use. FDA approved drugs i.e. non-pegylated liposomal (Myocet ® ) and pegylated liposomal (Doxil ® ) formulations have no doubt shown comparatively reduced cardiotoxicity, but has raised new toxicity issues. The entrapment of DOX in biocompatible, biodegradable and safe nano delivery systems can prevent its degradation in circulation minimising its toxicity with increased half-life, enhanced pharmacokinetic profile leading to improved patient compliance. In addition, nano delivery systems can actively and passively target the tumour resulting increase in therapeutic index and decreased side effects of drug. Foreseeing the need of a comprehensive review on DOX nanoformulations, in this article we for the first time have given an updated insight on DOX nano delivery systems.